Features of formation and functioning of ruling elite in the context of patronal presidentialism in Turkmenistan - Осадчук, І. Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Concepts of political class, political elite, ruling class, ruling elite, patronal presidentialism are analysed. The role of the president and his entourage during the formation of the ruling elite of Turkmenistan is ascertained. Features of functioning of ruling elite in the context of patronal presidentialism in Turkmenistan are defined.